Biomimicking Fiber Platform with Tunable Stiffness to Study Mechanotransduction Reveals Stiffness Enhances Oligodendrocyte Differentiation but Impedes Myelination through YAP‐Dependent Regulation. Issue 37 (12th August 2020) - Ong, William; Marinval, Nicolas; Lin, Junquan; Nai, Mui Hoon; Chong, Yee‐Song; Pinese, Coline; Sajikumar, Sreedharan; Lim, Chwee Teck; Ffrench‐Constant, Charles; Bechler, Marie E.; Chew, Sing Yian
Abstract: A key hallmark of many diseases, especially those in the central nervous system (CNS), is the change in tissue stiffness due to inflammation and scarring. However, how such changes in microenvironment affect the regenerative process remains poorly understood. Here, a biomimicking fiber platform that provides independent variation of fiber structural and intrinsic stiffness is reported. To demonstrate the functionality of these constructs as a mechanotransduction study platform, these substrates are utilized as artificial axons and the effects of axon structural versus intrinsic stiffness on CNS myelination are independently analyzed. While studies have shown that substrate stiffness affects oligodendrocyte differentiation, the effects of mechanical stiffness on the final functional state of oligodendrocyte (i.e., myelination) has not been shown prior to this. Here, it is demonstrated that a stiff mechanical microenvironment impedes oligodendrocyte myelination, independently and distinctively from oligodendrocyte differentiation. Yes‐associated protein is identified to be involved in influencing oligodendrocyte myelination through mechanotransduction. The opposing effects on oligodendrocyte differentiation and myelination provide important implications for current work screening for promyelinating drugs, since these efforts have focused mainly on promoting oligodendrocyte differentiation. Thus, the platform may have considerable utility as part of a drug discovery program in identifying molecules that promote both differentiation and myelination. Abstract : Changes in tissue stiffness are hallmarks of neural pathologies that may hinder the regenerative process. The development of an artificial axon platform with tunable stiffness to study mechanotranduction allows independent analysis of axon structural and intrinsic stiffness effects on oligodendrocyte myelination. Opposing effects on oligodendrocyte differentiation and myelination provide important implications for current work screening for promyelinating drugs.